Dynamic Analysis and Synchronization of Two Uncoupled Chaotic Hindmarsh-Rose Neurons - Nguyen, Le Hoa (Old Journal, 2019)
In this paper, the problem of synchronization of two uncoupled chaotic Hindmarsh-Rose (HR) neurons is addressed. First, the dynamic behaviors of a single HR neuron stimulated by an external applied current are studied. By using the concept of fast/slow dynamic analysis, the bursting mechanism of the HR neuron is investigated. Considering the applied current as a bifurcation parameter, the chaotic behavior as well as other dynamic behaviors is reported. Second, the author formulated a method for synchronization of two uncoupled chaotic HR neurons. By using a Lyapunov function, a nonlinear feedback control law is designed that guarantees that the two uncoupled neurons are globally asymptotically synchronized. Finally, in order to verify the effectiveness of the proposed method, numerical simulations are carried out, the results of which are provided herein.